The Development of British civil affairs and its employment in the British sector of allied military operations during the Battle of Normandy, June to August 1944 - Flint, E R (Department of Applied Science, Security and Resilience, 2009)
Civil Affairs and its more robust sibling, Military Government, were military organisations designed to ensure that basic civil order and welfare were maintained in those allied and enemy states encountered on operations during the Second World War. In so doing, they enabled formation commanders to focus on defeating enemy forces without being distracted by possible civilian problems. Using the battle of Normandy as a case study, this research assesses the utility of Civil Affairs in supporting military needs during operations. This contrasts with previous studies that concentrate on aspects of social and diplomatic history. If the need for Civil Affairs was generally axiomatic, there was much debate as to the extent and method of delivery required. Civil Affairs quickly recognised that in dealing with direct problems such as “disorganisation, disease and unrest” it was necessary for seemingly indirect aspects of civilian life to be maintained. Various forms of bureaucratic friction resulted and several Civil Affairs approaches were used, before the model for the North West Europe campaign was agreed. Nevertheless, the organisation employed in Normandy was arguably the most extensive and best prepared of the war. However, it also had to deal with many different civilian problems and in trying military circumstances. Consequently, the battle is fertile ground for the examination of the extent and nature of the organisation’s operational utility. Using primary and secondary sources, this paper argues that Civil Affairs was militarily both useful and necessary. Furthermore, it was able to provide wider diplomatic and political benefits as well as serving core military needs. The research concludes by acknowledging that whilst mistakes were made, the various improvements made to Civil Affairs in preparation for, together with the lessons learnt during, Normandy stood the organisation in good stead for the significantly larger problems encountered later in the war.
Keywords: Normandy (France) - History, Military; World War, 1939-1945; Defence policy - United Kingdom; British civil affairs; World War, 1939-1945 - Campaigns - France - Normandy; Allied military operations